2020
DOI: 10.1111/sms.13636
|View full text |Cite
|
Sign up to set email alerts
|

Merging self‐reported with technically sensed data for tracking mobility behavior in a naturalistic intervention study. Insights from the GISMO study

Abstract: Sound exposure data are central for any intervention study. In the case of utilitarian mobility, where studies cannot be conducted in controlled environments, exposure data are commonly self‐reported. For short‐term intervention studies, wearable devices with location sensors are increasingly employed. We aimed to combine self‐reported and technically sensed mobility data, in order to provide more accurate and reliable exposure data for GISMO, a long‐term intervention study. Through spatio‐temporal data matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The aim of this study was to synthesize and critically review the available intervention studies on active commuting and beneficial health effects before the publication of the GISMO study (Sareban et al, 27 Reich et al, 28 Niederseer et al, 29 Loidl et al, 30 Schmied et al, 31 Neumeier et al, 32 Fernandez La Puente de Battre et al, 33 Sareban et al, 34 Reich et al, 35 ). Only eight articles on a total of six studies were detected, and the researchers reported a diverse range of results relating to active commuting type, duration, and output 16‐23 .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to synthesize and critically review the available intervention studies on active commuting and beneficial health effects before the publication of the GISMO study (Sareban et al, 27 Reich et al, 28 Niederseer et al, 29 Loidl et al, 30 Schmied et al, 31 Neumeier et al, 32 Fernandez La Puente de Battre et al, 33 Sareban et al, 34 Reich et al, 35 ). Only eight articles on a total of six studies were detected, and the researchers reported a diverse range of results relating to active commuting type, duration, and output 16‐23 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants were active even during wintertime and did not use their cars more often than during summer. A detailed analysis on the seasonal aspects of active commuting in the GISMO study is provided elsewhere 26 . This is in contrast to Stigell et al 38 who found lower cycling frequencies during winter than during summer.…”
Section: Discussionmentioning
confidence: 97%
“…Participants were asked to wear these devices during 2 weeks at the beginning and 2 weeks toward the end of the intervention period. With this combined approach, the validity of the mobility documentation could have been increased substantially compared to self‐reported approaches 26 …”
Section: Methodsmentioning
confidence: 99%
“…Each subject kept a diary to evaluate distances covered during active commuting. Additionally, subjects were given a wearable device with an integrated GPS tracker and optical heart rate sensor (Polar M200, Polar Electro Oy, Finland) for two weeks at the beginning as well as at the end of the study, to validate diary entries 17 …”
Section: Methodsmentioning
confidence: 99%